Detection of SARS-CoV-2 from Indonesia with colorimetric saliva based RT-LAMP method using thermal cycler - Arif Bimantara; Ika Afifah Nugraheni; Luluk Rosida; Tasya Muliasari (International Journal of Health Science and Technology, 2022)
Coronavirus disease 2019 (COVID-19) is an acute respiratory syndrome disease caused by the SARS-CoV-2 virus (severe acute respiratory syndrome coronavirus 2). This virus has mutations that cause its transmission to speed up so it requires a fast detection method to prevent such transmission. The detection method that becomes gold standard is RT-qPCR (reverse transcription-quantitative polymerase chain reaction). The disadvantage of the RT-qPCR method is that the long detection time and nasopharyngeal swab sampling cause discomfort in the patient. One alternative method of detection of the SARS-CoV-2 virus is colorimetric saliva based RT-LAMP (reverse transcription loop-mediated isothermal amplification). The advantage of the RT-LAMP method is that it is fast and accurate. The purpose of this study is to determine the ability of the RT-LAMP saliva-based colorimetric method to use thermal cyclers as an alternative to SARS-CoV-2 detection in Indonesia. This study used the primary design of SARS-CoV-2 Indonesia. The samples used were positive and negative saliva for COVID-19 based on RT-qPCR test results from PKU Muhammadiyah Hospital, Yogyakarta City. The research stages include optimization of RT-LAMP conditions, saliva sampling followed by colorimetric visualization of results and electrophoresis. Colorimetric testing was carried out with the addition of phenol red and observed a change in color from pink to yellow. The results showed that RT-LAMP can run optimally at 65 °C for 45 minutes. Colorimetric RT-LAMP testing in this study was ineffective because it could not detect positive samples compared to electrophoresis results. Factors that cause this include a small number of amplicons, incompatible RT-LAMP reagents used for colorimetric methods using phenol red, and phenol red which cannot work optimally so that it requires a new or more appropriate pH indicator. It is necessary to conduct further research by replacing other visualization methods such as replacing pH indicators or by fluorescence methods.